Parental Catastrophizing and Goal Pursuit in the Context of Child Chronic Pain: A Daily Diary Study - Caes, Line; van Gampelaere, Cynthia; Van Hoecke, Eline; Van Winckel, Myriam; Kamoen, Kristien; Goubert, Liesbet (Frontiers in Psychology, 2021)
Background: Despite daily variability in children's chronic pain experiences, little is known about how parents' emotions and goals toward their child's pain are influenced by these daily changes. This diary study examined how daily child pain intensity (as perceived by parents) moderates the associations between parental catastrophic thoughts about child pain on the one hand, and daily parental distress and parents' goals with regard to their child's pain (pain control vs. activity engagement) on the other hand. Method: Participants were 25 parents of 20 different children (N = 18; 90% girls). Children, aged 8–14 years (M = 9.5, SD = 2.09), experienced either chronic headache or functional abdominal pain with an average pain duration of 22.5 months (SD = 24.5 months). Daily parental responses (i.e., perceived child pain intensity, distress and goal endorsement) were collected through a 3-week daily diary (resulting in 413 valid diary reports). Parents completed the Pain Catastrophizing Scale for Parents prior to starting the diary (PCS-P general) and a daily measure (PCS-P daily) included in the diary. To account for the interdependence of the data, the data were analyzed using multilevel modeling. Results: Perceived daily child pain intensity moderated the impact of parental general and daily catastrophic thoughts on parents' daily distress. Only for parents experiencing low general catastrophic thoughts an increase in distress was observed on days when they perceived their child's pain intensity as high. For all parents, high levels of perceived child pain intensity were related to more distress on days where parents reported high levels of catastrophic thinking (i.e., PCS-P daily). Perceived daily child pain intensity also moderated the impact of parental general catastrophic thinking on parents' daily endorsement of goals. Parents with high levels of general catastrophic thinking reported a lower focus on child pain control on days when child pain intensity was perceived to be low. Parents with low general catastrophic thinking reported lower endorsement of the activity engagement goal on days where the child's pain intensity was perceived to be low. Conclusion: These findings highlight the complexity of daily fluctuations in parental distress and goals regarding their child's pain. Clinical implications and future directions are critically assessed.